Recent changes to virus taxonomy ratified by the International Committee on Taxonomy of Viruses (2022) - Walker, Peter J. (2022)
Funding Information: E.M.A. gratefully acknowledges funding by the U.K. Biotechnology and Biological Sciences Research Council (BBSRC); this research was funded by the BBSRC Institute Strategic Programme Gut Microbes and Health BB/R012490/1 and its constituent projects BBS/E/F/000PR10353 and BBS/E/F/000PR10356. B.E.D. is supported by the European Research Council (ERC) Consolidator grant 865694: DiversiPHI and the Deutsche Forschungsgemeinschaft (DFG, German Research Foundation) under Germany’s Excellence Strategy – EXC 2051 – Project-ID 390713860. This work was supported in part through Laulima Government Solutions, LLC prime contract with the US National Institute of Allergy and Infectious Diseases (NIAID) under Contract No. HHSN272201800013C. J.H.K. performed this work as an employee of Tunnell Government Services (TGS), a subcontractor of Laulima Government Solutions, LLC under Contract No. HHSN272201800013C. A.R.M. is a Program Director at the U.S. National Science Foundation (NSF); the statements and opinions expressed herein are made in a personal capacity and do not constitute endorsement by NSF or the government of the United States. H.M.O. was supported by the University of Helsinki and Academy of Finland by funding for FINStruct and Instruct Centre FI, part of Biocenter Finland and Instruct-ERIC. D.L.R. is supported by the U.K. Medical Research Council (MC_UU_1201412). R.J.O. and D.B.S. were supported by the Wellcome Trust (WT108418AIA). S.S. acknowledges support from the Mississippi Agricultural and Forestry Experiment Station (MAFES), USDA-ARS project 58-6066-9-033 and the National Institute of Food and Agriculture, U.S. Department of Agriculture, Hatch Project, under Accession Number 1021494. E.J.L, D.M.D. and R.C.H were supported by the National Institute of Allergy and Infectious Diseases of the National Institutes of Health under Award Number U24AI162625. Except for Donald M. Dempsey, R. Curtis Hendrickson, Richard J. Orton and Donald B. Smith, the authors were members of the ICTV Executive Committee during the relevant period. The views and conclusions contained in this document are those of the authors and should not be interpreted as necessarily representing the official policies, either expressed or implied, of the US Department of Health and Human Services, or of the institutions and companies affiliated with the authors. The findings and conclusions in this report are those of the authors and do not necessarily represent the official position of their affiliates, including the Centers for Disease Control and Prevention. For the purpose of open access, the authors have applied a Creative Commons Attribution (CC BY) licence to any Author Accepted Manuscript version arising from this submission. Publisher Copyright: © 2022, This is a U.S. Government work and not under copyright protection in the US; foreign copyright protection may apply.